Support Needs of Indian Women in Early Labour - Panda Sunita; D’Sa Juliana; C Rao Anitha (Journal of Women's Reproductive Health, 2016)
The study was conducted in four selected hospitals in the Southern part of India with an aim to determine the support needs of women in early labour as perceived by women. A descriptive design was used to determine the support needs of women in early labour. Following ethical approval, sixty women between 29-40 weeks of gestation with singleton pregnancy were interviewed in early labour, using a validated Labour Support Need Assessment Tool to gather data on background information and perception of women related to need and support needs (physical, emotional and informational support). Results indicated that women perceived all types of support such as physical, emotional and informational as significant factors in their care during labour, regardless of their parity and gestation. The major findings of the study suggested that there was a slightly higher need for support among women for informational (90.33%) and emotional support (88.78%) compared to physical support (80.19%). For primigravid women, and multiparous women who were experiencing labour for the first time (previous birth by caesarean section), the ‘need for support’ was greater than for women who had previous experience of labour. Early labour is the time when most women use their own coping skills and seek support. Determining the quantity and quality of support women need at this phase of labour can help care providers to provide the best comprehensive care to women in early labour. The findings of the study provide a guide on what women feel is helpful in early labour.
Keywords: Early labour